Complicaciones maternas en gestantes hospitalizadas por infección SARS-CoV-2 atendidas en el Hospital Regional de Loreto, 2020 - Román Ruiz, Brayan Alexis (2022)
Studies involving patients with COVID-19 who are pregnant are still limited and their association remains unclear, especially in the Loreto region where no reports have been made on it. Therefore, the present work aims to determine maternal complications in pregnant women hospitalized for SARS-CoV-2 infection treated at the Loreto Regional Hospital, 2020. A descriptive study was carried out in 53 53 pregnant women diagnosed with COVID-19. Concluding that regarding the clinical characteristics, respiratory compromise (13.2%), headache (9.4%), cough (9.4%), fever (9.4%), nasal congestion (7.5%) and sore throat (1.9%) were observed. 88.7% did not require oxygen, 5.7% required noninvasive ventilation, and 5.7% required invasive ventilation. 83% presented an asymptomatic infection and 9.4% severe infection. 39.6% of the patients had a cesarean delivery, of which 90.5% were due to obstetric causes and 9.5% due to COVID-19 pneumonia. Among the maternal complications, it was observed that 58.5% did not present complications (31/53), within the complications presented, preeclampsia (11.3%), death (9.4%, 5/53), dysfunctional labor (7.5%), fetal distress (7.5%), mechanical ventilation (5.7%), stillbirth (5.7%), premature rupture of membranes (3.8%), vaginal bleeding (1.9%), threatened abortion (1.9%), abortion (1.9%), eclampsia (1.9%) and sepsis (1.9%).